Description of Patient Satisfaction Levels in the Aspects of Facilities, Empathy, and Assurance for Dental Health Services at the Bandung Dental Health Clinic during the Adaptation of New Habits in the Era of the Covid-19 Pandemic - Dewi Sodja Laela; Anggina Sekar Fatharani; Nurul Fatikhah; Sekar Restuning (Institute of Computer Science (IOCS), 2022)
Dental and oral health services at various health care facilities during the Covid-19 pandemic implemented stricter security procedures with health protocols set by WHO. Various rules that must be carried out by the center of health care facilities in preventing the transmission of Covid-19 can have an impact on patient satisfaction. Assessment of patient satisfaction indicators include tangible, empathy, assurance, reliability and responsiveness. This study aims to determine the level of patient satisfaction with dental health services at the Bandung Dental Health Clinic during the adaptation of new habits in the Covid-19 pandemic era in terms of facilities, empathy and assurance. This type of research is analytic with a cross sectional design. Samples were patients who received health services at the JKG Clinic, Poltekkes Kemenkes Bandung, selected by purposive sampling as many as 40 respondents. Data obtained from questionnaires through google form. Analysis of hypothesis testing using Spearman Rank correlation. The results of this study indicate that the level of patient satisfaction in terms of facilities, empathy and assurance at the JKG Clinic, Poltekkes, Ministry of Health, Bandung, is in the very satisfied category with scores between 87.5% - 95%. Spearman Rank correlation analysis with p value = 0.000 <0.05, shows that there is a relationship between the level of patient satisfaction with aspects of facilities, empathy and guarantee of dental health services. The correlation coefficient value of the facility aspect to satisfaction is 0.519 which means that the relationship is strong and the correlation coefficient value of empathy and assurance aspects to satisfaction is 0.707, which means the relationship is very strong. The conclusion of this study is that the level of patient satisfaction with dental health services at the Bandung Dental Health Clinic during the adaptation of new habits in the Covid-19 pandemic era is related to aspects of facilities, empathy and assurance.